SELECTIVE MODAL ANALYSIS OF POWER FLOW OSCILLATION IN LARGE SCALE LONGITUDINAL POWER SYSTEMS - -, Wirindi; Ari Nrartha, I Made; -, Soedjatmiko (Jurnal Teknologi Elektro; Vol 8 No 1 (2009): Jurnal Teknologi Elektro, 2012)
Novel selective modal analysis for the determination of low frequency power flow oscillation behaviour based on eigenvalues with corresponding damping ratio, cumulative damping index, and participation factors is proposed. The power system being investigated consists of three large longitudinally interconnected areas with some weak tie lines. Different modes, such as exciter modes, inter area modes, and local modes of the dominant poles are fully studied to find out the significant level of system damping and other factors producing power flow instability. The nature of the energy exchange between area is determined and strategic power flow stability improvement is developed and tested.